A Novel Rotation-Structure Based Stick-Slip Piezoelectric Actuator with High Consistency in Forward and Reverse Motions - Jizhou Tang; Jingsong Wei; Yuming Wang; Zhi Xu; Hu Huang (Actuators, 2021)
Under the same driving voltage and frequency, the forward and reverse motion inconsistency of stick-slip piezoelectric actuators would bring difficulty for subsequent control. To solve this problem, a rotation-structure based piezoelectric actuator with completely symmetric structure and two driving feet was initially proposed. By testing its output performances under various driving voltages and frequencies, it was confirmed that, although similar speeds could be achieved for forward and reverse motions, the maximum displacement and backward displacement in each step were still quite different. By analyzing the reasons leading to this difference, this actuator was further improved by using only one driving foot. The experimental results showed that the forward and reverse motion consistency of the improved actuator had been significantly improved. The deviation rate was only 1.6%, corresponding to a travel distance of 118.7 μm, obtained under the driving voltage of 100 V and driving frequency of 10 Hz. The comparison with some previously reported actuators further confirmed the advancement of this improved actuator.